2018
DOI: 10.12991/mpj.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and predator scent tests alter brain BDNF levels differentially according to gender, in rats and effects of fluoxetine

Abstract: We compared different stress conditions on brain BDNF levels, in rats exposed to social isolation test (SIT) and predator scent tests (PST). BDNF expression in the frontal cortex, hippocampus, and amygdala was compared, and effects of chronic fluoxetine (FLU) treatment were evaluated. Rats were exposed to SIT and PST for one month. FLU was given (5 mg/kg/day, ip) throughout stress procedures. Controls, stress, and treatment groups were evaluated in elevated plus maze, anxiety scores were calculated. BDNF expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 20 publications
(24 reference statements)
4
3
1
Order By: Relevance
“…It has been shown that both the antidepressant drug fluoxetine and exercise are able to increase BDNF expression in the brain exposed to stress [ 26 , 28 , 36 ], and our results are consistent with these findings. In this regard, exercise induces BDNF enhancement during extinction consolidation and, consequently, reduces threat expectancies following reinstatement in PTSD [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It has been shown that both the antidepressant drug fluoxetine and exercise are able to increase BDNF expression in the brain exposed to stress [ 26 , 28 , 36 ], and our results are consistent with these findings. In this regard, exercise induces BDNF enhancement during extinction consolidation and, consequently, reduces threat expectancies following reinstatement in PTSD [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings were similar to that in male PTSD animals in our previous study [ 26 ]. BDNF changes after stress have been frequently reported in several studies [ 28 31 ] and our study confirms these findings. Since BDNF has been shown to have an essential role in mediating stress-related pathophysiological changes in the brain [ 32 ] these findings are expectable.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations